Assessing pastoral reforms through the performance of Agro-Pastoral Community-Based Organizations in south Tunisia - Sghaier, Mariem; Frija, Aymen; Postigo, Julio; Speelman, Stijn; Alary, Veronique; Sghaier, Mongi (Elsevier, 2025)
Pastoralism is one of the most important agricultural production systems in drylands worldwide. It plays an important role in both the economy and the cycle of ecosystem goods and services. However, it is vulnerable to climatic challenges such as prolonged drought and socioeconomic pressures such as administrative shortcomings and ineffective governance. Under neoliberal influence, political and economic reforms have been implemented over the last 30 years to address these threats. These reforms have promoted local institutions for rangeland management and agro-pastoral development. In this paper, we assess the impact of these reforms on pastoral devolvement and Community-based natural resource management (CBNRM) by analyzing the performance of agro-pastoral community-based organizations CBOs in the province of Médenine (south-eastern Tunisia). We use a two-step methodology, with the first step focusing on a quantitative typology analysis of the performance of 31 CBOs. In a subsequent qualitative step, data from semi-structured interviews with 21 CBO chairpersons were used to identify the drivers of CBO performance. Results show that only 10% of the CBOs studied are able to move towards autonomy and proper integration into local and regional institutional networks and development dynamics. About 42% of the CBOs need further support and are in a precarious situation as they are dependent on public support. The remaining 48% have a low growth potential and in the early stages of consolidation. The qualitative analysis suggests that these shortcomings are mainly related to the CBOs' lack of networking skills. In addition, CBOs should improve their reputation and gain more trust from pastoral communities. Our findings suggest that well-functioning institutions do contribute to rural development; however, the design of pastoralist policy and institutional reforms should include long-term complementary support for the institutions created and consideration of the pastoralist community and regional contexts in order to achieve long-lasting transformative outcomes.